Dietary Patterns vs. Dietary Recommendations - De Cosmi, Valentina; Mazzocchi, Alessandra; Milani, Gregorio P.; Agostoni, Carlo (Frontiers in Nutrition, 2022)
Dietary Reference Values (DRVs) are important for developing labeling laws, identifying populations at risk of over- or under-consumption and promoting public health interventions. However, the process of developing DRVs is quite complex, and they should not be viewed as recommendations ready to use or goals for individuals. Rather, they require interpretation by professionals and can form the basis of dietary advice. On the other hand, a focus on foods rather than macronutrients can assist individuals in understanding a healthy diet, taking into consideration many variables that may help compliance with a healthy dietary style. Evolution, tradition within specific geographical and historical contexts, taste, economic affordability, season-associated local dietary resources and lifestyle may all explain the increasing popularity of dietary patterns that are highly successful today. Three models (Mediterranean, New Nordic and Japanese) have been recently characterized as for geographical setting and food composition, as well as for the associated lifestyle. Of note, all these three models rely on pyramids sharing a large basis made up by local vegetal resources and a top of red meats (allowed in any cases, but in limited amounts), thus allowing for the urgent demand of sustainability for the planet’s health. This mini review aims to summarize the meaning of DRVs, and to describe the dietary patterns that better contemplate health, diet diversity and sustainability.